Distribution characteristics of nitrogen and the related microbial community in the surface sediments of the Songhua River. Issue 43 (5th August 2021) - Li, Congyu; Zhong, Zhen; Wang, Wenfu; Wang, Haiyan; Yan, Guokai; Dong, Weiyang; Chu, Zhaosheng; Wang, Huan; Chang, Yang
Abstract : In this study, temporal and spatial distribution of nitrogen in the Songhua River sediments and distribution characteristics of related microbes as well as the relationship between them were investigated. Abstract : Nitrogen in surface sediments is becoming an ecological risk to the river environment and it is essential to clarify the relationship between the different forms of nitrogen and related microorganisms. A survey was conducted to analyze the distribution characteristics of the nitrogen and related microbial community in the sediments of the Songhua River during normal season and dry season. In the surface sediments of the Songhua River, no total nitrogen (TN) pollution risk was observed according to the U.S. EPA assessment criteria (1000 mg kg −1 ) for sediment contamination, but TN in several sampling sites (554.9–759.7 mg kg −1 ) exceeded the alert values (550 mg kg −1 ) should be concerned according to the guidelines issued by the Ministry of Environment and Energy of Ontario, Canada. The average TN, NH4 + –N, NO3 − –N and total organic nitrogen (TON) in the surface sediments of the Songhua River during normal season were higher than those in the dry period. TON was the main form of nitrogen in the sediment of Songhua River, NO2 − –N content was lowest and no obvious difference was observed between normal and dry seasons. The highest average NH4 + –N of both seasons occurred in the Nenjiang River, and the highest average NO3 − –N of both seasons were found in the main stream of the Songhua River. The community abundance of AOB genes (1.1 × 10 7 to 2.5 × 10 8 copies per g soil in normal season, 7.2 × 10 5 to 3.3 × 10 8 copies per g soil in dry season) was higher than that (1.2 × 10 6 to 9.7 × 10 7 copies per g soil in normal season, 6.6 × 10 4 to 3.2 × 10 7 copies per g soil in dry season) of AOA genes in both normal and dry seasons. The denitrifying nirS genes were predominant in both seasons, and their abundance (1.8 × 10 6 to 8.0 × 10 8 copies per g soil) in dry season was higher than that (9.7 × 10 5 to 4.6 × 10 8 copies per g soil) in normal season. Moreover, the moisture concentration, pH, dissolved oxygen and different formation of nitrogen were key factors affecting the variation of nitrogen-transformation microorganisms during normal and dry seasons. This research could help to explain the relationship between nitrogen transformation and the related microbial community in the surface sediment, which could provide a scientific basis for water ecological restoration and water environment improvement of Songhua River.